1970
DOI: 10.1002/j.2050-0416.1970.tb03254.x
|View full text |Cite
|
Sign up to set email alerts
|

Organoleptic Trials With Hop Bitter Substances

Abstract: Pure hops-derived substances were added to unhopped beer. Illumination only produced a sun-struck flavour with cfs-isohumulone, trans-isohumulone and racemic trans-isohumulone. It seems that 3-methyl-butenyl-mercaptan is not or not alone responsible for sun-struck flavour.Tests trials show that trans-isohumulone, cis-tsohumulone, racemic trans-iso humulone, trans-pt-isohumulone and ds-^-isohumulone do not show significant differences in bitter taste and bittering power. Fresh solutions of these bitter acids ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…It has been proposed that iso-␣-acids are the most important source of bitterness in beers 10,24 . Lager 16, with the lowest iso-␣-acids, had the highest total content of tetrahydroiso-␣-acids of all the products.…”
Section: Hplc Of Beer Bitterness Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that iso-␣-acids are the most important source of bitterness in beers 10,24 . Lager 16, with the lowest iso-␣-acids, had the highest total content of tetrahydroiso-␣-acids of all the products.…”
Section: Hplc Of Beer Bitterness Acidsmentioning
confidence: 99%
“…These compounds exist as the equally bitter cis-and trans-isomers. Iso-␣-acids are thought responsible for 70% of observed sensory bitterness 23,24 . In beer, trans-iso-␣-acids are less stable then cis-iso-␣ acids during aging 4 due to their lower aqueous solubility 3 ; ␤-acids are believed to contribute little to the bitterness perception in comparison with ␣-acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of bitterness has been related to the concentration of iso-α-acids [24,27,28,31,32]and to a lesser extent with the alcohol content in beer [33]. In particular, the iso-α-acids are responsible for approximately 70% of the bitterness of beer [34,35,36,37]. It is generally recognised that the main bittering principles of beer are the hop-derived iso-α-acids [38].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the photolysis occurs with light of a rather long wavelength (day light) and exclusively with iso-a-acids. 3 The reasons for this are not obvious. The result of our efforts however indicate that only 3-methyl-2-butene-l-thiol was formed and therefore the results of the Japanese research group have been confirmed.…”
Section: Introductionmentioning
confidence: 99%